Academic, Social, and Financial Changes in International Students’ Lives Due to the COVID-19 Pandemic - Filippou, Kalypso (Helsinki University Press, 2025)
During the COVID-19 pandemic, multiple measures were established that influenced international students’ academic, financial, and social activities. Focusing on international students who studied in Finland, we collected quantitative data with an online survey (n = 192) to increase our knowledge of the students’ experiences and to compare the students’ responses based on their level of study. The results indicated that financial difficulties varied significantly between the groups of students, whereas academically and socially, they were more similar. The financial situations of bachelor’s and master’s degree students were more severely affected than were those of exchange students and doctoral researchers. These findings illustrate variations between different groups of international students, even though they are often presented as one single group. Although both heterogeneity and homogeneity were observed between the groups of international students, all displayed academic resilience, in spite of the stress and challenges they experienced.